Neighborhood Material Deprivation Is Associated with Childhood Asthma Development: Analysis of Prospective Administrative Data. (19th May 2019) - Simons, Elinor; Dell, Sharon D.; Moineddin, Rahim; To, Teresa
Abstract : Rationale . Material deprivation has been proposed as a more comprehensive measure of socioeconomic status than parental income. Stronger associations between childhood emergency department visits for asthma and air pollution have been demonstrated among children living in neighborhoods with high levels of deprivation, but the associations with asthma development and ongoing asthma are not known. Objectives . We determined the associations between neighborhood material deprivation and the development of new and ongoing childhood asthma. Methods . Prospectively collected administrative data housed at the Institute for Clinical Evaluative Sciences were examined for Toronto children born from 1997 to 2003. Neighborhood material deprivation, comprising no high school graduation, lone parent families, government transfers, unemployment, low income, and homes needing major repairs, was reported in the Ontario Marginalization Index. Incident asthma was defined by the time of entry into the Ontario Asthma Surveillance Information System (OASIS) database. We measured the risk of incident asthma using Cox proportional hazards models and the associations between ongoing asthma visits and deprivation by year of life with generalized linear mixed models. Results . OASIS asthma criteria were met for 21% of the 326, 383 children. After adjustment for characteristics strongly associated with asthma, including male sex, prematurity, obesity, and atopic conditions other than asthma, children with high birth neighborhood deprivation were at increased risk of incident asthma (HR 1.11; 95% CI, 1.09–1.13). High deprivation in a given year of life was associated with increased odds of ongoing asthma during that year of life (OR 1.03; 95% CI, 1.02–1.05). Conclusions . Children living in high-deprivation neighborhoods are at increased risk of incident and ongoing asthma. This study suggests that neighborhood material deprivation may represent a helpful tool for evaluating the effects of disparities in health and social advantages on the likelihood of developing and continuing to need healthcare visits for ongoing childhood asthma.